Intelligent and open new generation telecom service architecture and its key technologies - Jianxin LIAO; Hao ZHANG; Tong XU; Lingfei NI; Jingyu WANG; Wenfu WU (Dianxin kexue)
For complex heterogeneous networks,IOTSA (intelligent and open telecom service architecture) based on the comprehensive decoupling of service systems was proposed,as well as core mechanisms such as intelligent scheduling of network resources,dynamic service orchestration and combination,and intelligent monitoring of abnormal behavior.Through the establishment of a three-level interface and four-layer capability opening architecture,multi-granular capability opening and comprehensive resource sharing were realized,which met the needs of multiple scenarios.Key technologies such as low-risk and low-cost rapid decoupling of service systems and dynamic coordination of multiple services were proposed.These achievements had formed a series of international standards and had been applied on a large scale on existing networks.By providing a large number of ultra-fine-grained capabilities,396 atomic capabilities,and flexible composite capabilities,the development of operator and third-party services and applications were strongly supported.